Ethological behavior of Bos taurus, Bos indicus, and Caqueteño Creole cattle in three tree cover systems of Brachiaria decumbens paddocks at the Amazon foothills in Colombia - Londoño-Paéz, Sandra Milena; Orjuela-Chaves, Jose Alfredo; Álvarez-Carrillo, Faver; Suarez-Salazar, Juan Carlos; Vasquez-Gamboa, Lucena; Ortiz-Meneses, Jhoyner Felipe; Parra, Gustavo Adolfo Celis (Revista de Ciências Agroveterinárias, 2022)
The study was conducted at the Amazon Research Center CIMAZ - MACAGUAL of the University of Amazonia, Colombia, with a tropical rain forest climate (Af). The behavior of Bos taurus, Bos indicus, and Caqueteño Creole cattle, the animals were observed in paddocks with three levels of scattered tree cover density. The pasture was composed of Braquiaria decumbens with 35 days of regrowth. Direct observations were made from 9:00 a.m. to 5:00 p.m. with 10-minute intervals between the recording of the activities. The activity performed most often during the day by all of the animals was grazing under the sun, and those who pasture the most are the Caqueteño Creole, followed by the Bos indicus and, finally, the Bos taurus. Ruminating was the second most important activity performed by the cattle, having presented the same tendency. In the paddocks with a low level of tree cover, the animals pasture more in the shade; this trend is more relevant among B. taurus cattle. Caqueteño Creole cattle dedicate less time to water consumption and rest, spending more time grazing, in the high and medium cover levels, they interrupt the grazing at noon for a shorter time compared to B. indicus and B. taurus; after 2 p.m., the creoles vertiginously increase grazing. At the high cover level, the peak of grazing of the Caqueteño Creoles is at 9 a.m. and from 1-1:30 p.m., while at the medium tree cover level, the peak of pasturing was at noon, 1:30 p.m., and 4:30 p.m., at the high tree level of cover, the peak for the three breeds was at 11 a.m. Only at the average tree level of cover did the Caquetaño creoles and B. indicus present a similar peak. In 9-9:30 a.m. and 4-5 p.m., the breeds substantially reduce rumination.